2017
DOI: 10.2298/pac1702120c
|View full text |Cite
|
Sign up to set email alerts
|

First-principles studies on band structure and mechanical properties of BiFeO3 ceramics under high pressure

Abstract: Mechanical properties and band structure of rhombohedral BiFeO3 nanostructures were studied using density functional theory for different pressures in the range from 0 to 50GPa. The elastic constant of BiFeO3 nanoceramics was determined and different moduli were calculated for various applied pressures. The bulk (B) and shear (G) modulus show an increasing trend on applied high pressure. The findings of the present work also confirm that the hardness of BiFeO3 increases with the applied press… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…[ 43,44 ] This effect is also used to deagglomerate nanometer‐size materials. Though the pressure provided by ultrasonicator (135 MPa) is not enough to distort the pristine crystal structure (rhombohedral; R 3 c ) of BFO, [ 45 ] ultrasonication (480 W, 40 kHz) can induce a piezoelectric effect in presence of light irradiation. When a ferroelectric material, like MDT doped‐BFO NPs, experiences a hydrostatic stress, the induced displacement of ions causes an alteration in the polarization resulting in a release of the screening charges that can participate in the catalysis ( Figure ).…”
Section: Discussionmentioning
confidence: 99%
“…[ 43,44 ] This effect is also used to deagglomerate nanometer‐size materials. Though the pressure provided by ultrasonicator (135 MPa) is not enough to distort the pristine crystal structure (rhombohedral; R 3 c ) of BFO, [ 45 ] ultrasonication (480 W, 40 kHz) can induce a piezoelectric effect in presence of light irradiation. When a ferroelectric material, like MDT doped‐BFO NPs, experiences a hydrostatic stress, the induced displacement of ions causes an alteration in the polarization resulting in a release of the screening charges that can participate in the catalysis ( Figure ).…”
Section: Discussionmentioning
confidence: 99%
“…The values obtained for the elastic constants (table 1) are relatively low, corresponding to about 40% of the values reported for BiFeO 3 [36] and 95% of those reported for DyFeO 3 (R = rare earth) [37], but are in agreement with values obtained for ferromagnetic Fe-based complex perovskites [6]. Similarly, defining the elastic compliance constants as the reciprocals of the elastic constants, S ij = 1/c ij , the bulk and shear moduli of Reuss B R and G R [38] are defined as follows: The effective bulk modulus that evaluate the resistance of material to a change in volume, and the shear modulus that characterizes the change in shape that an elastic material undergoes when subjected to shear stresses, are calculated through the arithmetic average of the above equations ( 2)-( 5) [39], i.e.…”
Section: Mechanical Propertiesmentioning
confidence: 63%
“…To study the nature of the material, electronic band structure is plotted along high symmetry directions in the first Brillouin zones. It is observed that the valance band crosses the Fermi level and touches the conduction band showing no band gap between valance band and conduction band above Fermi level . The size of the circles used in character bands in Figure gives information about the relative contribution from the corresponding bond.…”
Section: Resultsmentioning
confidence: 99%